VALUASI EKONOMI PADA KAWASAN DESTINASI WISATA ALAM CIBULAN KABUPATEN KUNINGAN PERSPEKTIF MAQASHID SYARIAH - Dewi Fatmasari; Hafni Khairunnisa; Yati Haryati (IAIN Syekh Nurjati Cirebon, 2023)
AbstractThe increase in the number of tourists is directly proportional to the impact of the damage. To minimize the impact of tourism, an economic valuation of natural tourist destinations is needed to obtain additional economic benefits for conservation. Economic valuation is carried out using the Travel Cost Method. The purpose of this study is to analyze the factors that influence the willingness to pay tourists at the Cibulan Nature Tourism Destination and to estimate the economic value of the Cibulan Nature Tourism Destination using the Travel Cost Method. The research method used is descriptive quantitative with data analysis techniques in the form of multiple linear regression analysis, travel cost method, and consumer surplus. The results showed that travel cost, age, distance, and facilities had a significant influence on the level of visits to Cibulan tourism objects, while income and education did not have a significant influence on the level of visits to Cibulan attractions. The total economic value obtained is Rp. 148,157,850,203 per year. Willingness to pay following Maqashid Sharia and bring benefits to the community.Keywords: Economic Valuation; Travel Cost Method; Consumer Surplus.